A Study Protocol for the Management of Children With Juvenile Idiopathic Arthritis Based on ePROs - Shen, Biyu; Shi, Songsong; Cui, Hengmei; Li, Yunyun; Chen, Haoyang; Jin, Huan; Xu, Jia; Liu, Zuojia; Jin, Yanliang (Frontiers in Pediatrics, 2022)
Background: Juvenile idiopathic arthritis (JIA) is a common chronic rheumatic disease with no known cures, affecting children with the age of onset under 16 years. Patient-reported outcomes (PROs) measures are an important basis for evaluating the impact of JIA and associated therapies, however, which is particular challenge in the pediatric setting. At present, no randomized controlled studies have investigated the effect and usability of ePROs symptom management for children with JIA. Methods: This longitudinal, randomized, controlled trial will be carried out at outpatient and pediatric wards of the Shanghai children’s medical center affiliated to Shanghai Jiao Tong University School of Medicine. One hundred children with JIA diagnosed according to the International League of Associations for Rheumatology (ILAR) patients are randomized to receive individualized symptom management based on ePROs or routine management. The primary outcome is the mean C-Ped-PROMIS T-scores of patients in the ePROs-based group and the control group. The secondary outcomes are the trajectories of C-Ped-PROMIS T-scores and HRQOL scores, and changing relationship between them. Data were collected at 5 time points: at enrollment (“baseline”) and at the time of follow-up visits scheduled at 1, 3, 6, and 12 months. Discussion: Findings are expected to conclude that the symptom management based on ePROs for children with JIA can improve the symptom of JIA, it’s a feasible and effective way to monitor and intervene children with JIA. Clinical Trial Registration: The study was registered on Chinese Clinical Trial Registry (ChiCTR2100050503), http://www.chictr.org.cn/showproj.aspx?proj=132769.